Perceptions of AETCOM module amongst medical students: a questionnaire-based study - Jaiswal, Kavita M.; Abraham, Jijo Philip; Chowhan, Karra Rahul (International Journal of Basic & Clinical Pharmacology, 2025)
Background: The Attitude, Ethics and Communication (AETCOM) module is a cornerstone of competency-based medical education (CBME), implemented in the medical curriculum. It aims to instill effective patient communication skills in students. The present study evaluates students’ perspectives on the implementation of the AETCOM module. Methods: This cross-sectional questionnaire-based study was conducted through Google form filling in 2nd phase MBBS students. Questions about knowledge attitudes and perspectives about the implementation of the AETCOM module in their MBBS curriculum were assessed. Results: 172 students filled out the Google forms with a response rate of 86%. 169 (98.25%) students felt that it was essential to learn this module. 170 (98.83%) opined that ethics in medical practice is very important and learning it will help them in their future practice of medicine. 34% students reported of getting burdened in exams. Students preferred case-based scenarios and role plays most effective methods of learning. 53.5% of participants felt both summative assessment (SA) and formative assessment (FA) are essential for the complete evaluation of AETCOM competencies. Conclusions: The participants reported inclusion of AETCOM is important because it helped them improve their communication skills and good relationships build with doctors. 34% of participants reported being stressed during exams due to the burden of the already existing heavy curriculum. These findings draw the attention of all stakeholders for a revision in the implementation of the module to ease learning. Students think that even though time-consuming, conducting both FA and SA is justifiable.